Clinical characteristics and outcomes of relapsed follicular lymphoma after autologous stem cell transplantation in the rituximab era. Issue 2 (30th January 2020) - Sesques, Pierre; Bourcier, Jessie; Golfier, Camille; Lebras, Laure; Nicolas‐Virelizier, Emmanuelle; Hacini, Maya; Perrin, Marie Claire; Voillat, Laurent; Bachy, Emmanuel; Traverse‐Glehen, Alexandra; Moreau, Anne; Martin, Laurent; et al.
Abstract: High‐dose chemotherapy followed by autologous stem cell transplantation (ASCT) is a therapeutic option for patients with relapsed follicular lymphoma (FL). The clinical characteristics and outcomes of FL relapse after ASCT in the rituximab era have not yet been fully elucidated. We retrospectively reviewed 414 FL patients treated with ASCT between 2000 and 2014 in four hematology departments. All patients received rituximab as a first‐line treatment. We specifically analyzed the clinical characteristics, treatment strategies at relapse, and outcomes of 95 patients (23%) who relapsed after ASCT. The patients (median age, 57 y) received a median of two lines of therapy (range, 2‐6) prior to ASCT, with 92% in complete response (CR) or partial response (PR) before ASCT. Histological transformation at relapse after ASCT was observed in 20% of the patients. Treatment at relapse after ASCT consisted of chemotherapy with or without rituximab (n = 45/90, 50%), targeted agents (18%), rituximab monotherapy (14%), or consolidation allogeneic transplantation after induction chemotherapy (12%) and radiotherapy (6%). After relapse, the median progression‐free survival (PFS) and overall survival (OS) were 1 year (95% CI, 0.541‐1.579) and 5.5 years (95% CI, 1.910‐9.099), respectively. In the multivariate analysis, histological transformation (HT) was associated with OS ( P = .044; HR 2.439; 95% CI, 1.025‐5.806), and a high FLIPI score at relapse was associated with PFS ( P = .028; HR 2.469; 95% CI, 1.104‐5.521). This retrospective study showed that the period of PFS of patients who relapsed after ASCT is short. A biopsy should be performed for these patients to document the HT. Our results indicate that new treatment strategies will need to be developed for these patients.